Animating inquiry-based teaching in grade-school classrooms - Shelly Kinash (The Canadian Network for Innovation in Education (CNIE), 2008)
This paper describes interpretive empirical research with five teachers who: a) articulate their pedagogy as defined by an inquiry-based stance, b) use digital technologies within their teaching, and c) engaged in online and/or face-to-face professional development with the Galileo Educational Network (GENA). Four questions guided the inquiry: what does inquiry mean to teachers; what is it like to be an inquiry-based teacher; what supports teachers in fostering inquiry, and; what is the relative impact of the three models of supports offered through GENA - face-to-face only, online only, and combination face-to-face and online. Analysis revealed that meaningful and regular connection with GENA staff serving an animation role superseded the support model; it did not matter whether the supports were provided at a distance or face-to-face. Recommendations derived from the experiences of the five teachers inform the professional supports necessary to nurture teachers' inquiry-based stance and approaches. Résumé: Cet article décrit une étude empirique interprétative réalisée avec cinq enseignants qui a) articulent leur pédagogie autour de l'investigation, b) utilisent des technologies numériques pour enseigner, et c) se sont impliqués dans du développement professionnel en ligne ou en face à face avec le Galileo Educational Network (GENA). Quatre questions ont guidé l'enquête : que veut dire investiguer pour les enseignants, que veut dire être un enseignant utilisant l'investigation, qu'est-ce qui soutient les enseignants dans leur encouragement de l'investigation, et, quel est l'impact relatif des trois modèles de soutien offerts par l'équipe de GENA, face à face, en ligne et une combinaison face à face et en ligne. L'analyse a révélé qu'un lien significatif et régulier avec l'équipe de GENA, qui joue un rôle d'animation, remplace le modèle de soutien. Il importait peu que le soutien soit offert à distance ou en face à face. Des recommandations découlant des expériences des cinq enseignants nous informent du soutien nécessaire pour encourager les enseignants utilisant des approches par investigation.